The Balkan Entente in Turkish–Yugoslav relations (1934–41): the Yugoslav perspective. Issue 6 (1st November 2016) - Barlas, Dilek; Vlašić, Anđelko
ABSTRACT: By discussing the role of the Balkan Entente within Turkish–Yugoslav relations, this article endeavours to reflect the extent to which the Entente guaranteed security to Turkey and Yugoslavia. It deals with the 1934–41 period, which starts with the formation of the Balkan Entente and ends with the German invasion of Yugoslavia. The article is written mainly based on Yugoslav archival documents and aims to provide an alternative narrative that contests the conventional Turkish view. It also demonstrates that although the political leaders in Turkey and Yugoslavia became more optimistic about the future of the region after having signed the Balkan Entente, their perception of threat changed over time during the period of increasing instability in Europe.